Prezi and new technologies to strengthen training processes: Analysis of teaching practice in students of the Baccalaureate - Genoveva Zambrano Romero, Merly; Moisés Benavides Bailón, Jeovanny (International Journal of Psychosocial Rehabilitation, 2020)
The use of information and communication technologies in various areas it has generated controversy about the benefits or harm that may be caused by being incorporated into the educational field. This article seeks to determine the conditions for the use of this type of technology and especially the Prezi tool in high school students. The current challenge is faced with the application of this type of technology as a didactic resource and its educational use. The medium indicates the communication process while technology is responsible for providing the material support of the process; both with the same importance, being necessary to work with the communicative process that helps all learning and studies the types of instruments that will be used and the strategies of use. To achieve the development of this article, a bibliographic review of all the material available in reliable sources was carried out to be able to issue conclusions.